5q11.2 deletion syndrome revisited—Further narrowing of the smallest region of overlap for the main clinical characteristics of the syndrome - Bayat, Allan; Bayat, Michael; Broers, Chantal; Polstra, Abeltje M.; Zwijnenburg, Petra J. G.; Hjortshøj, Tina Duelund (American journal of medical genetics. Part A, 2021)
Microdeletions at 5q11.2 are rare. Subjects show a phenotypic spectrum that overlaps CHARGE syndrome and 22q11.2 deletion syndrome. A growing number of subjects present with learning difficulty and/or intellectual disability, immune deficiency, congenital heart malformation, and dysmorphism. DHX29 and IL6ST have been proposed as candidate genes for the development of the major clinical manifestations. We present a new case and narrow down the shortest region of overlap to evaluate possible candidate genes. Our case does not present developmental delay or immune deficiency indicating a reduced penetrance for some of the main clinical manifestations. The shortest region of overlap between subjects with deletions at 5q11.2 is approximately 450 kb (position 54.3–54.7 Mb). The narrowed region comprises 10 protein coding genes, including DHX29. DHX29 is a strong candidate gene for the main features of 5q11.2‐microdeletion syndrome; however, our findings suggest a joined impact of several genes as the cause of the syndrome.